PKM KELAS IBU HAMIL DALAM UPAYA MENINGKATKAN KESEHATAN IBU DAN JANIN DI POSYANDU MELATI DESA BUKIT KRATAI WILAYAH KERJA UPT BLUD PUSKESMAS RUMBIO - Fitri Apriyanti; Dhini Anggraini Dhilon (Universitas Pahlawan Tuanku Tambusai, 2021)
Pregnancy is a beautiful period experienced by every woman, but major changes in the body in a short time can cause some disturbances and complaints that reduce enjoyment during pregnancy (Suananda, 2018). Changes that occur in pregnant women include physical and psychological changes. The changes that occur are caused by an increase in hormones, namely the hormones estrogen and progesterone, resulting in psychological aspects and various problems arise in pregnant women, namely anxiety (Suristyawati, et al, 2019). The purpose of this community service is to conduct class activities for pregnant women to improve maternal and fetal health. The methods used are counseling, prenatal yoga activities and hypnotherapy. The result of this community service is that the success of the target number of participants taking classes for pregnant women can be said to be very good. Participants who were invited based on the direction of the Village Midwife (100%) could attend the training activities, namely as many as 20 pregnant women. In conclusion, the PKM Class for Pregnant Women has been carried out in an Effort to Improve Maternal and Fetal Health on 10 – 17 July at the Melati Posyandu, Bukit Kratai Village, the Working Area of the UPT BLUD Puskesmas Rumbio. It is hoped that this service program can be followed up elsewhere in the following year to improve the health and welfare of the mother and fetus during pregnancy.